Cystic ovarian disease in a crossbred cow - MEHROTRA, S; AGARWAL, S K; SHANKER, UMA; HOQUE, M (The Indian Journal of Animal Reproduction, 2005)
Management of cystic ovarian disease in a crossbred cow is reported in present paper.